Pengaruh Media Pembelajaran Power Point Terhadap Motivasi Belajar Mahasiswa Program Studi Pendidikan Ekonomi di Universitas Muhammadiyah Maumere - Renya Kuki, Elisabeth (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
This research aims to determine the influence of powerpoint- based learning media as a learning media used by lecturers. The approach used is through descriptive qualitative methods. This research was conducted in the V semester economics study program, Muhammadiyah University, Maumere, Suruber. The data in this research were obtained from informants through lecturer in office management courses in semester V and srudents in the economics education study program in semester V. Data collection techniques were obtained using interviews and questionnaires. The results of this research indicate the need for learning media to support the learning process so that students become clear and motivated. Use of powerpoint media. It is used in lerning and makes it easier for office management course lecturers to deliver material in the V semester economics education study program. Apart from that, the use of powerpoint media has a significant influence on students of the economics education study program at Muhammadiyah University, Maumere. In this way, the powerpoint media has an influence on the learning motivation of students in the V semester economics education study program.